Piper guineense (Swhan and Thon) Inhibits Lanosterol-14α-demethylase in Multi-Drug Resistant Non-albicans Candida Species: In vitro and In silico Studies - Olumide Oluyele; Damilola Alex Omoboyowa; Ayomide Esther Aderogba; Koffi Adusa Osei (Advances in Medical, Pharmaceutical and Dental Research)
Candida species are globally recognized for invasive infections with poor prognosis. Burgeoning quest for the discovery of novel therapeutics has increased the scientific scrutiny of several medicinal plants. This study assessed the efficacy of Piper guineense crude extract and fractions against selected multi-drug resistant non- albicans Candida species. Both the crude and fractionated extracts of P. guineense elicited marked anti-candidal activity. Overall, the crude extract showed better efficacy over the fractions with the highest inhibition zone (25.0mm) recorded against Candida tropicalis; amongst the fractions, n-hexane fraction (F2) produced the highest inhibition zone (23mm) against Candida glabrata. The MIC ranged from 25mg/ml to 50mg/ml; while the MBC ranged between 100 mg/ml to 200 mg/ml. HPLC analysis revealed the presence of 14 compounds in the extract, with prominent members being quercetin, ellagic acid, persin, catechin, p-coumaric acid, and lutein. The binding affinity and free binding energy results reveal that most of these bioactive compounds were better than the standard drug (Fluconazole). Conclusively, P. guineense extracts demonstrated impressive anti-candidal properties against the tested multi-drug resistant non-albicans Candida species and could have potential as new drug lead for the treatment of infections resulting from these pathogens. Received on, 17 October 2024 Accepted on, 15 January 2025 Published on, 15 March 2025